PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN KANTOR DIREKSI PT PERKEBUNAN NUSANTARA VII BANDAR LAMPUNG - Fala, Sofi Elisa Nurul; Nugraha, Adia; Endaryanto, Teguh (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
This research aims to examine  job satisfaction, motivation, and employee performance, and to analyze the effect of job satisfactionand motivation on employee performance. The data collection was conducted at PT Perkebunan Nusantara VII Bandar Lampung Head Office from February to March 2022. The method utilized in  this research was survey method by involving 54 samples of employees from 10 divisions. The samples in this  study were employees of group  III. The data survey  were analyzed using descriptive analysis and multiple linear regression analysis. The results show that employee job satisfaction is  categorized as quite good, employee motivation is  quite good, and employee performance is  categorized as good. It is concluded that job satisfaction and employee motivation have a significant and partial effect on the employee performance of PTPN VII employees group III.  Key words: employee performance, job satisfaction, motivation